Forensic Assessment of Trauma Using Periodontal Tissues Evaluation: possibilities and future perspectives (Bulletin of the International Association for Paleodontology, 2024)
The article reviews the emerging field of periodontal tissue analysis in the context of forensic trauma assessment. Periodontal tissues are examined for their unique potential to improve the accuracy and scope of forensic investigations. They respond dynamically to different types of injuries, exhibiting distinct histological changes and features, thereby providing insights into the nature of injuries and their timing. Although this method is promising, it also poses notable challenges, including contamination risks, post mortem changes, and interpretation of histological results. Future implications focus on advances in molecular analysis, integration of imaging technology, and establishment of reference databases. Standardization, quality assurance, and interdisciplinary collaboration are essential to ensure reliable periodontal tissue analysis. In summary, periodontal tissue analysis is a dynamic and promising tool with significant implications in the forensics, provided it is used ethically and in accordance with the highest standards. This emerging field highlights the use of periodontal tissue analysis and commitment of forensic experts needed to unravel the complexities of trauma, offering a potential path in the field of forensic science.